ANALISIS PERKEMBANGAN PELAKSANAAN PERSILANGAN SAPI MADURA DENGAN SAPI LIMOUSIN DI PULAU MADURA (The Development Analysis the Crossing of Madura x Limousin Cattle Implementation in Madura Island) - F. Kutsiyah; Sholeh Sholeh; Moh. Zali; Yudi Heryadi (Jurnal Ilmu dan Teknologi Peternakan, 2018)
This paper presents a description of performance and development of crossbreed (madura cattle x limousine cattle) implementation. The research method used survey, direct field observation and literature study (The results of previous research began in 1998 or for almost two decades since the program was applied). The location of research in the crossbreed central area of madura island such as Gili Iyang island (crossbreeding centre in Sumenep regency), Larangan and Kadur district fattening zone in Pamekasan regency), Camplong and Jrengik district in Sumenep regency; meanwhile Galis and Kokop district in Bangkalan regency. Data were analyzed by using descriptive statistic. The results showed that Madura Island was adaptive for first generation madrasin cows (G1) and not adaptive for G2 or G3. For the sustainability of Madura cattle population, inseminators are not allowed to inseminate crossing cattle with limousine straw